Hubungan Pemberian Makanan Tambahan (PMT) terhadap Status Gizi Kurang pada Balita - Irmayani; Wahdaniyah; Supyati (Nutrition Science and Health Research, 2023)
Adequate nutrition for toddlers is crucial, especially during the First 1000 Days of Life, to support optimal growth and development. Malnutrition in toddlers can lead to issues such as stunting, wasting, and increased disease risk. This study aims to determine the effect of supplementary feeding (PMT) on the nutritional status of undernourished toddlers in the Katumbangan Health Center area. The research used a quantitative method with a pre- experimental one-group pretest-posttest design. The population consisted of 42 undernourished toddlers aged 11-59 months, also used as samples through total sampling. Data were collected through anthropometric measurements of weight and height before and after the 30-day PMT intervention. Data analysis used the Wilcoxon test to identify differences in nutritional status before and after the intervention. The results showed a significant improvement in nutritional status after PMT, with 47.6% of the toddlers improving from malnourished to normal status. Statistical tests showed a p-value of 0.002, indicating a significant difference. In conclusion, PMT is effective in improving the nutritional status of toddlers, and it is recommended to continue the program to reduce the prevalence of malnutrition in the area.